Gouvernace mondiale - Aglietta, Michel; Pisani-Ferry, Jean; Bureau, Dominique; Tubiana, Laurence; Boisson, Thomas; Jacquet, Pierre; Allard, Patrick (Paris : La Documentation française, 2002)
Bibliotheek François Vercammen
Frans
Monografie